Survival and transmission fitness of SARS-CoV-2 over the time-of-flight in an aerosolization chamber - Yiying Zhang; Justin M. Donovan; Dylan W. Weninger; Victor Lam; Richard Gibson; Steven Renaud; Daniel Paquette; Alex Lescanec; Cody Hird; Christopher T. DeGroot; Jessica L. Prodger; Franco Berruti; et al. (npj Viruses)
Abstract The impact of various environmental factors on SARS-CoV-2 transmission remains debated, partly due to limited physical experiments with infectious virus that closely replicate real-world conditions. Using a novel, self-contained containment level 3 chamber, we aerosolized the virus in different environmental conditions then collected droplets on nasal tissue, cell lines, or different materials to measure the transmission of infectious SARS-CoV-2. We found that SARS-CoV-2 survival was much shorter than previously reported for the potential of fomite transmission. Temperature, relative humidity and the presence of incinerated tobacco, cannabis, or vape products had no discernible impact on SARS-CoV-2 transmission through aerosolized droplets, but affected the survival of VSV, a non-respiratory enveloped virus. When compared to USA-WA1/2020 and the Omicron variant, Delta SARS-CoV-2 had the greatest survival during aerosolization. These findings suggest that respiratory enveloped viruses like SARS-CoV-2 may have and may be continuing to evolve higher transmission fitness through droplets.